2018
DOI: 10.5267/j.ac.2018.3.002
|View full text |Cite
|
Sign up to set email alerts
|

A structural equation model for evaluating user’s intention to adopt internet banking and intention to recommend technology

Abstract: Although several prior research projects have focused on the factors that impact on the adoption of information technology, there are limited empirical research works that simultaneously capture technology factors (UTAUT2) and customer specific factors (perceived technology security and intention to recommend) helping users adopt internet banking. Thus, the current study aims to develop an integrated technology adoption model with extended UTAUT model and perceived technology security to predict and explain us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 23 publications
5
85
0
1
Order By: Relevance
“…The result indicated that all constructs met the minimum requirement of 0.7 (Rahi, Ngah, & Ghani, 2018). Moreover the reliability of individual items was assessed by investigating the factor loading of all variables with their corresponding constructs.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The result indicated that all constructs met the minimum requirement of 0.7 (Rahi, Ngah, & Ghani, 2018). Moreover the reliability of individual items was assessed by investigating the factor loading of all variables with their corresponding constructs.…”
Section: Measurement Modelmentioning
confidence: 99%
“…Therefore, effort expectancy is explained as the degree of ease associated with the use of the system (Venkatesh et al , 2003). Several researchers have investigated technology adoption issues in online retailing using UTAUT model (Chiu and Wang, 2008; Marchewka et al , 2007; Rahi, Ghani, Alnaser and Ngah, 2018; Rahi, Ghani and Ngah, 2018). Therefore, less has been noticed about integration of information technology models that combine social psychological factors (service quality) and technology-related constructs (performance expectancy and effort expectancy).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interoperability will become a permanent issue of research and experimentation since heterogeneity and constant change will persist for the foreseeable future (Cheni & Doumeingts, 2005). Therefore, this study aimed to find out factors that may influence the intention to use for mobile money service interoperability using Technology Acceptance Model (TAM), D&M IS success model and The Task-Technology Fit (TTF) to help develop not only practical useful models but also provide a basis for gaining a deeper understanding of strong correlations among factors that influence the usage of mobile money services and get better exploratory power than the individual theory use (Dahlberg et al, 2015;Rahi et al,2018a;Anouze & Alamo, 2020). For example, Chale & Mbamba (2014) combined TAM, DoI, and UTAUT theories to provide a basis for a deeper understanding of SMEs' need to continue using mobile money to enhance their businesses.…”
Section: Statement Of the Problemmentioning
confidence: 99%